Poison ivy : how elite colleges divide us - Mandery, Evan J. (The New Press, 2022)
"An eye-opening look at how America's elite colleges and suburbs help keep the rich rich--making it harder than ever to fight the inequality dividing us today"-- Provided by publisher.
Keywords: Universities and colleges -- United States -- Admission.; Education, Higher -- Social aspects -- United States.; Education, Higher -- Economic aspects -- United States.; Elite (Social sciences) -- United States.; Income distribution -- United States.; Universités -- États-Unis -- Admission.; Enseignement supérieur -- Aspect social -- États-Unis.; Enseignement supérieur -- Aspect économique -- États-Unis.; Élite (Sciences sociales) -- États-Unis.; Revenu -- Répartition -- États-Unis.; EDUCATION / General.; Education, Higher -- Economic aspects; Education, Higher -- Social aspects; Elite (Social sciences); Income distribution; Universities and colleges -- Admission; United States; EDUCATION / Schools / Levels / Higher